2012
DOI: 10.1080/19404476.2012.11462092
|View full text |Cite
|
Sign up to set email alerts
|

Effective Science Instruction: Impact on High-Stakes Assessment Performance

Abstract: This longitudinal prospective cohort study was conducted to determine the impact of effective science instruction on performance on high-stakes high school graduation assessments in science. This study provides powerful findings to support authentic science teaching to enhance long-term retention of learning and performance on state-mandated assessments. Students experienced some combination of zero to three effective teachers throughout their middle school experience. Findings revealed that all students who e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Cooperative learning has long been valued in education because of its positive results on students' academic achievement as well as affective domains (Hall, 1989;Michaelsen, Knight, & Fink, 2004). Collaborative learning refers to students working together toward a common goal in small groups (Johnson, Zhang, & Kahle, 2012) and emphasizes collaboration, teamwork, and student interaction (Duch, Groh, & Allen, 2001;Prince, 2004).…”
Section: Collaborative Teamworkmentioning
confidence: 99%
“…Cooperative learning has long been valued in education because of its positive results on students' academic achievement as well as affective domains (Hall, 1989;Michaelsen, Knight, & Fink, 2004). Collaborative learning refers to students working together toward a common goal in small groups (Johnson, Zhang, & Kahle, 2012) and emphasizes collaboration, teamwork, and student interaction (Duch, Groh, & Allen, 2001;Prince, 2004).…”
Section: Collaborative Teamworkmentioning
confidence: 99%
“…As other lessons are taught, educators should look for opportunities to connect students' prior learning on weather and climate science to other subjects. These three recommendations should make the lessons stronger in experiential (Morpus, 2017), inquiry-based (Johnson et al, 2012), problem-solving (Cheng et al, 2018), and cooperative or team-based learning (Gonzalez, 2018;Lin, 2006;Morpus, 2017;Terada, 2017) and more thoroughly use the formative worksheets the students completed (McDaniel et al, 2011) and writing to learn strategies (Gonzalez, 2018) that are reported in our literature review to enhance learning retention.…”
Section: Discussionmentioning
confidence: 99%
“…To increase learning retention, content must be reinforced and connections made to other knowledge (Terada, 2017;Willingham, 2015). Therefore, in the weather and climate curriculum, we employed a number of learning theories and strategies, in whole or in part, that are supported by the literature to improve science learning retention among middle school students: (a) experiential learning (Morpus, 2017), (b) inquiry-based learning (Johnson et al, 2012), (c) problem-solving learning (Cheng et al, 2018), (d) combining text with images in our visuals (Terada, 2017), (e) simulations and role-plays (Gonzalez, 2018), (f) formative assessments (i.e., worksheets for all lessons) (McDaniel et al, 2011); (g) cooperative or team-based learning (Gonzalez, 2018;Lin, 2006;Morpus, 2017;Terada, 2017), (h) writing to learn (e.g., writing hypotheses and conclusion statements) (Gonzalez, 2018), and (i) graphing exercises (Gonzalez, 2018).…”
Section: Figure 1 Yasc Conceptual Model For Improving Youth Science mentioning
confidence: 99%
“…Penelitian ini dilatar belakangi beberapa penelitian terdahulu, Newmann and Wehlage menemukan dalam Authentic Teaching and Learning dapat mengarahkan berpikir struktur siswa untuk meraih substansi, inovasi dan prestasi belajar, pembelajaran ini dilakukan dalam kelas [1]. Peneliti lain telah mempertimbangkan siswa dapat mengekplorasi konsep authenticity dengan menggunakan pendekatan AI [2]; [3]; [4]; [5].…”
Section: A Latar Belakangunclassified